The Concept of Attitude and Knowledge in the Book of Riyadh Ash-Shalihin by Imam Nawawi and Its Implementation in Curriculum Design - Abu Darda; Serene Fawwaz Afinandya; Muhammad Thoriqul Islam; Ahmad Wahyulil Albab; Habib Bawafi (JURNAL ASIMILASI PENDIDIKAN, 2026)
This study examines the book Riyadh al-Shalihin by Imam Nawawi, one of the classical works that has significantly influenced Islamic literature, particularly in the development of ethical teachings. The book presents a collection of hadiths that emphasize the values of adab, which serve as an essential foundation in Islamic education and character formation. In the context of globalization and rapid technological development, Islamic education plays an increasingly important role in shaping the moral character of Muslim individuals. This study aims to analyze the concepts of adab and knowledge presented in Riyadh al-Shalihin and their implications for the design of an Islamic education curriculum, focusing on educational objectives, learning processes, and evaluation systems that can cultivate knowledgeable and well-mannered students. Using a literature study method, the research analyzes various relevant sources, including books and historical documents. The findings indicate that an education model grounded in adab and knowledge implemented through the internalization of moral values, teacher role modeling, and a curriculum that integrates theory with daily practice can effectively enhance students’ understanding and application of Islamic teachings. Furthermore, integrating religious and general knowledge into the curriculum contributes to a broader, more relevant learning experience. Further studies are recommended to deepen the development of learning processes and evaluation models in curricula inspired by Riyadh al-Shalihin.